What Does ASEAN Economic Community Bring to Older Workers? Examining Inequality in Old Age in Thailand’s Fast-Ageing Society - Wenqian Xu; Sikander Islam (JAS (Journal of ASEAN Studies), 2019)
The ASEAN Economic Community is envisaged to promote economic integration initiatives to create a single market across Southeast Asian member countries. It is acknowledged that the intergovernmental initiatives need to be accommodative to national and regional contexts. Thailand, as a pivotal and active partnership, endeavours to facilitate economic transformation and regional integration within the ASEAN and cope with population ageing in Thai society. Since Thailand has been the third most rapidly ageing country in the world, demographic changes pose new challenges for how to achieve persistent economic growth, productive employment and decent work. This article is based on a qualitative approach to investigate the emergent inequality within and across age cohorts shaped by the AEC structural forces, as well as utilizes reliable secondary data to formulate argumentation, including academic publications, policy analysis, scientific reports. We are particularly concerned about the heterogeneity and poverty in old age from the perspective of cumulative advantages/disadvantages. In conclusion, this article suggests policy recommendations of mitigating inequality in old age and advocates a critical lens to examine how political economic structure shapes older individuals in the labour market.